PS-P09-6: KNOWLEDGE, ATTITUDES AND PRACTICE OF SALT INTAKE AND BLOOD PRESSURE LEVEL IN A MULTI-ETHNIC POPULATION IN MALAYSIA. (January 2023) - Chew, Ming Tsuey; Chia, Yook Chin; Oui, Jethro Ee Keat; Ching, Siew Mooi; Devaraj, Navin Kumar; Lim, Hooi Min; Chew, Bee Nah; Mohamad, Mohazmi; Ooi, Pei Boon; Be, Hooi Chin
Abstract : Knowledge, attitudes and practice of salt intake and blood pressure level in a multi-ethnic population in Malaysia Objective: A changing lifestyle in the transition from a developing to a more developed country has led to increases in obesity, physical inactivity and unhealthy diet, including high salt intake. Studies have shown that salt consumption is high in Asia, but little is known about the practice among different ethnic groups. This study aimed to examine the knowledge, attitudes and practice of salt intake among Malaysian adults by different ethnic groups. Design and method: Participants aged =  > 18 years were recruited during a blood pressure health screening campaign from various centres. All participants completed a questionnaire that capturing information on socio-demographics, knowledge, attitudes and practice about salt consumption. Weight and height were measured and seated blood pressure (BP) measurements using an oscillometric sphygmomanometer were taken twice and averaged. Hypertension is defined as a systolic BP = > 140mmHg and/or diastolic BP = > 90 mmHg. Results: A total of 5128 participants were included in the study. The mean age of the participants was 39.5 ± 17.4 years and 59.6% were female. The mean SBP was 121.4 ± 17.6 mmHg and mean DBP 75.5 ± 11.1 mmHg. 61.5% knew the correct amount (< = 5 g) of daily dietary salt intake and 8.4% did not think it was important to reduce salt intake. 68.6% took measures to control salt intake; 69.9% avoided/minimized canned food, only 34.2% look at the salt labels and less than a third do not add salt during cooking, used spices during cooking and avoid eating in outlets and all of these practices were statistically significant between ethnic groups (p < 0 .001). Knowledge, attitude and practice of not reducing high intake of dietary salt does contribute to raise high BP as shown in Table 1. Conclusion: Our study reported that good knowledge does not translate into the desired attitude or practice of lower salt intake. More needs to be done to improve attitudes and behaviours about dietary salt intake, and to tailor it to different ethnic groups. This is warranted to prevent the increasing prevalence of hypertension.